Hundred years of economic relations between China and Great Britain, 1834-1934 - Chow, Pei-Gei (The University of Edinburgh, 1938)
The annual value of British trade with China is to be found in the reports of the British Board of Trade, but not prior to the year 1834, before which there were no figures for the British trade with China separate from those of Anglo Indian trade. Again, the whole of British trade with China should include Hongkong for reasons which we have given in our detailed statements.

Our detailed treatment of the importance of Britain in China's foreign trade can only begin with the year 1864 as since that year the trade figures have been regularly compiled by the Chinese Maritime Customs. But, in considering the movements of the chief goods between China and Hongkong, we have relied upon informations from the British side rather than upon those from the Chinese side because the British statistics give a reasonably reliable basis for analysis. The impor- tance of Great Britain in the foreign trade of China and the importance of China in the foreign trade of Great Britain are indicated in the actual figures which are given in the appendix.

As we have stated in detail before, the abolishment of the char- tered company's monopoly in trading with the Far East stimulated British export trade to China and her import trade from China. But, Anglo- Chinese trade remained undeveloped until 1843 during which year the monopoly of Chinese trade with foreigners was completely abolished, and trade between China and Britain was not confined to the city of Canton.

From 1865 many ports in China were thrown open to foreign trade and the trade between Britain and China then showed some increase. The period 1865 -1884 was a period of British commercial advance in China. But from 1885 until the end of the last century the general course of Anglo- Chinese trade was disfigured by years of retrogression for British trade began to feel some competition from other countries trading with China.

From the year 1834 to the last quarter of the nineteenth century, China's trade with Britain was limited to a small category of products, consisting chiefly of imports of cotton goods and woollen manufactures and exports of tea and silk. During the lineteenth Century the un- importance of China in the foreign trade of Britain is to be found in the fact that the balance of British trade with China relied upon exports of opium from India to China by the British traders.

When the present century opened its first quarter there was within the total volume of goods moving between Great Britain and China, a series of very considerable and significant changes. On the side of China's exports to Britain, tea met with strong competition, but there was not the same decline in silk. In the imports of China from Britain, cotton goods since 1885 remained the prime staple, holding the first place among goods which have grown in variety. In cotton manufactures exported from Britain to China, Britain early found her- self competing with Japanese cottons.

In the years from 1913 to 1914, China's demand for imported goods from Britain expanded and it was somewhat balanced by the discovery on the part of the British of large -scale uses for various Chinese natural products.

There developed a very important export of China to Britain in the shape of oil-bearing beans and seeds; animal products - hides, all of skins, wool and eggs which came to command an increasing market in Britain. Also, it is significant that iron and steel manufactures, electrical and chemical goods, and machines increased considerably in their percentage of the total imports of China from Britain. Railway building, and subsequently factory erection, created in their turn a demand for the importation of such goods, and for those which have still more recently extended to plants for industrial and municipal installations

Looking at the whole period of one hundred years from 1834 to 1934, there is no doubt that the increase in China's trade with Britain was steady in the forty years 1834 ®1874, and rapid just after the War period, but in the remaining years there are all the evidences of stagnation. As a whole, Great Britain certainly played an important role in the foreign trade of China. In the ten years 1884 ®1894, there was a turning point in Anglo ®Chinese trade as a whole, and since 1894 the excess of China's imports from Britain over her exports to Britain has been steady.

To go back to the early years of the century, Japan greatly increased her sere in China's trade and Britt in WEE no longer to retain her predominant position in China's foreign trade. During the postwar period Britain lust ground very considerably, while Japan and (50) probably the United States gained heavily. As Condliffe says: 10In part this changed direction of trade is due to the after -effects of the war period, but it is mainly due to more fundamental factors, such as the increased Pacific trade of America since the opening of the Panama Canal in 1913, the changed nature of the trade following upon local industrialization and the different pace of development in the various regions of China."

"Great Britain still remains the dominant factor in shipping though its position here also is weakening, while Japan is gaining and the United States is becoming a stronger competitor. It is probably indeed that it is only in respect of past investments that Great Britain . can claim to be the leading power in China to-day, and recent studies by C. F. Remer seem to indicate that even in this respect Japan's position is rapidly approaching that of its older rival."

I close this treatise with a sentence quoted from Professor Remer's remarks in order to indicate the importance of the present study. "The study of China's international economic relations meant until but Yesterday the study of British trade, British shipping, the (51) British business community, and British investments in China."